Nutritional Content of Dry Noodles Made from Mocaf Flour and Porang Flour and the Addition of Seaweed Extract - Savitri, Desta Malda; Dedin Finatsiyatul Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Dry noodles are fresh noodles that are dried until the water content reaches 8-10% by drying under sunlight or oven. This study used mocaf flour and porang flour, and the addition of seaweed. The use of mocaf flour as a substitute for wheat flour and porang flour to increase elasticity. The addition of seaweed is an alternative as a thickener for noodle base ingredients. The purpose of this study was to determine the effect of the treatment of the proportion of mocaf flour and porang flour and the addition of seaweed extract on physicochemical characteristics. This study aims to determine the characteristics of water content, ash content, protein content, fat content, and carbohydrate content of dry noodles with the proportion of mocaf flour and porang flour (60:40, 50:50, 40:60) and seaweed extracts (Sargassum sp., Eucheuma cottoni., and Ulva lactuca sp.). The research design used was a two-factor Completely Randomized Design (CRD) with two replications and then analyzed by ANOVA and DMRT 5%. The results of the analysis showed that the best treatment was in the proportion of mocaf flour and porang flour (50:50) and the addition of seaweed extract of Ulva lactuca sp. with a water content of 7.80%, ash content of 1.43%, protein content of 7.37%, fat content of 2.24%, carbohydrate content of 81.20%.